The effect of training loads on performance measures and injury characteristics in rugby league players: A systematic review - Booth, M.; Orr, R.; Cobley, S. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To conduct a systematic review into the effect of training load (TL) on both performance measures and injury characteristics in rugby league players. Methods: Based on PRISMA guidelines, a systematic search of electronic databases was performed from the earliest record to December 2016. Five electronic databases (MEDLINE, SPORTDiscus, CINAHL, Web of Science, and AusSportMed) were searched using keywords within the subcategories of population (rugby league players), intervention (training quantification), and outcomes (performance or injury). Original peer-reviewed published manuscripts were considered if they had a clear quantification of TL (eg, session rating of perceived exertion), clear measures of performance (tests of physiological parameters relative to rugby league players [eg, agility]), and/or injury characteristics (eg, injury incidence). Results: Twelve studies met the inclusion criteria. The highest TL was observed in preseason training phases. Higher TL elicited greater improvements in maximal aerobic power, vertical jump (in cm), and agility scores (in s). Higher TL was associated with higher incidence of muscular strains and joint sprains, lower-limb injuries, and overexertion and overuse injuries. Conclusions: Findings suggest a dose-response relationship between TL, physical performance, and injury characteristics. However, due to study and methodological limitations, the precise nature of this relationship is, as yet, inconclusive. Therefore, the development of uniform TL definition and quantification and further research is warranted.